THE ROLE OF TOURISM IN INCREASING TEXTILE EXPORTS - Suleymanova Shoira Alavhanovna (Scholar Express Journals, 2024)
The practice of attracting tourists to a country's textile industry, known as textile tourism, is gaining popularity and significantly impacts economic development. In today's world, tourism encompasses all sectors of the economy and has become a global business, promoting the growth of various industries. Increasing tourist flow plays a crucial role in preserving and popularizing historical landmarks, developing oriental cuisine, and promoting eco-friendly textiles produced in the country. In this regard, it is recommended that the government implements several supportive measures to strengthen the significance of the textile industry in the context of the growing tourism sector. Uzbekistan's textile industry is one of the most profitable, demonstrating significant economic results. This study aims to investigate the impact of tourist flow on the export of textile products manufactured in the country. The main goal of the research is to use empirical data to determine how the export of textile products from Uzbekistan is growing at a faster rate compared to the increase in tourist flow. The research, based on 572 observations, analyzes the export performance of Uzbekistan's textile industry and the impact of the tourism boom on it. The research employs methods such as regression analysis, correlation analysis, and panel data analysis to provide a comprehensive understanding of the relationships between tourism and textile exports. Tourism contributes not only to economic development but also to cultural exchange, positively influencing the country's reputation on the international stage. The growth of tourist flow leads to an increased demand for domestic products, including textiles, which in turn stimulates production development and improves product quality. The implementation of government support programs for the textile industry and tourism development can create new jobs, improve infrastructure, and attract investments to the region
Keywords: Textile Industry; textile industry's exports; tourism; GDP